Are We Forgetting About IgA? A Re‐examination of Coronavirus Disease 2019 Convalescent Plasma. Issue 6 (26th May 2021) - Verkerke, Hans; Saeedi, Bejan J.; Boyer, Darra; Allen, Jerry W.; Owens, Joshua; Shin, Sooncheon; Horwath, Michael; Patel, Kashyap; Paul, Anu; Wu, Shang‐Chuen; Wang, Jianmei; Ho, Alex; et al.
Abstract: Background: While convalescent plasma (CP) may benefit patients with COVID‐19, fundamental questions remain regarding its efficacy, including the components of CP that may contribute to its therapeutic effect. Most current serological evaluation of CP relies on examination of total immunoglobulin or IgG‐specific anti‐SARS‐CoV‐2 antibody levels. However, IgA antibodies, which also circulate and are secreted along the respiratory mucosa, represent a relatively uncharacterized component of CP. Study design and methods: Residual samples from patients and CP donors were assessed for IgM, IgG, and IgA anti‐SARS‐CoV‐2 antibody titers against the receptor‐binding domain responsible for viral entry. Symptom onset was obtained by chart review. Results: Increased IgA anti‐SARS‐CoV‐2 antibody levels correlated with clinical improvement and viral clearance in an infant with COVID‐19, prompting a broader examination of IgA levels among CP donors and hospitalized patients. Significant heterogeneity in IgA levels was observed among CP donors, which correlated weakly with IgG levels or the results of a commonly employed serological test. Unlike IgG and IgM, IgA levels were also more likely to be variable in hospitalized patients and this variability persisted in some patients >14 days following symptom onset. IgA levels were also less likely to be sustained than IgG levels following subsequent CP donation. Conclusions: IgA levels can be very heterogenous among CP donors and hospitalized patients and do not necessarily correlate with commonly employed testing platforms. Examining isotype levels in CP and COVID‐19 patients may allow for a tailored approach when seeking to fill specific gaps in humoral immunity.